Management accounting practices in selected Asian countries: A review of the literature - Sulaiman, Maliah; Nik Ahmad, Nik Nazli; Mohd Alwi, Norhayati (Emerald Group Publishing Limited, 2004)
Traditional management accounting techniques such as standard costing and variance analysis, traditional budgeting and cost volume profit analysis are said to be less useful in the present manufacturing environment. To succeed in the present dynamic business environment,tools or strategies such as JIT, ABC, TQM, process re-engineering, life cycle assessment and target costing would greatly enhance the ability of corporations to meet global competition. Through a literature review, this study examines the extent to which traditional and contemporary management accounting tools are being used in four Asian countries: Singapore, Malaysia, China and India. Overall, the evidence reviewed suggests that the use of contemporary management accounting tools is lacking in the four countries. The use of traditional management accounting techniques remains strong. The paper concludes with various recommendations for future research, the most important of which is the need for future studies to be grounded in theory.